South Park. Post Covid [videorecording (DVD)] - Parker, Trey, 1969-; Parker, Trey, 1969- (Paramount, 2022)
What happened to the children who lived through the Pandemic? Stan, Kyle, Cartman, and Kenny survived but will never be the same Post Covid. If Stan, Kyle, and Cartman could just work together, they could go back in time to make sure Covid never happened and save Kenny's life. In South Park: Post-COVID & The Return of COVID, traveling back to the past seems to be the easy answer until they meet Victor Chaos.